2020
DOI: 10.1212/wnl.0000000000010932
|View full text |Cite
|
Sign up to set email alerts
|

Small fiber pathology in autism and clinical implications

Abstract: ObjectiveTo investigate small-fiber innervation of the skin and its relationships with clinicometry of autism and peripheral afferents for contact heat-evoked potential (CHEP) and psychophysical measures of thermal thresholds.MethodsWe recruited 32 men with autism (26.5 ± 5.9 years) and conducted small fiber assessments of (1) skin biopsy with quantifying intraepidermal nerve fiber (IENF) density, (2) CHEP, (3) quantitative sensory testing, and large-fiber physiology of nerve conduction studies. Results were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…The majority of intellectually-abled (IQ > 70) autistic individuals tend to experience increased pain and touch sensitivity, particularly in areas innervated by small unmyelinated C-fibers [ 88 ]. Chien et al [ 91 ] reported the presence of small C-fiber pathology (denervation) in more than half of their adult male cases, a finding that shared a U-shaped relationship with autism severity. Another small study by Silva and Schalock [ 92 ] investigated C-fiber innervation in the skin of four autistic children with hypoesthesia and allodynia, again finding reduced density of nerve fibers within the regions studied.…”
Section: Symptom Overlap Between Autism and Ehlers-danlos Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The majority of intellectually-abled (IQ > 70) autistic individuals tend to experience increased pain and touch sensitivity, particularly in areas innervated by small unmyelinated C-fibers [ 88 ]. Chien et al [ 91 ] reported the presence of small C-fiber pathology (denervation) in more than half of their adult male cases, a finding that shared a U-shaped relationship with autism severity. Another small study by Silva and Schalock [ 92 ] investigated C-fiber innervation in the skin of four autistic children with hypoesthesia and allodynia, again finding reduced density of nerve fibers within the regions studied.…”
Section: Symptom Overlap Between Autism and Ehlers-danlos Syndromementioning
confidence: 99%
“…As discussed in the previous section, many autistic people display signs of small fiber neuropathy within the skin [ 91 , 92 ]. These same types of small unmyelinated C-fibers are intimately involved in the autonomic nervous system, suggesting that structural and functional damage may also be present within this system as well.…”
Section: Symptom Overlap Between Autism and Ehlers-danlos Syndromementioning
confidence: 99%
“…This effect may, however, depend on frequency and body site (26,30) and is not universally reported (28,32). Interestingly, some autistic adults may have diminished density of small intraepidermal nerve fibers, which was related to elevated sensory thresholds to thermal stimuli (33).…”
Section: Behavioural Thresholdsmentioning
confidence: 99%
“…After correcting for multiple comparisons, we found no significant correlations between hearing thresholds and AASP/SP auditory low threshold scores or SEQ auditory EP scores; between Von Frey thresholds and AASP/SP Tactile Low Threshold or SEQ overall EP scores; or between JVP dome thresholds and AASP/SP Tactile Low Threshold or SEQ overall EP scores, all Holm-Bonferroni corrected p's ≥ . 33.…”
Section: Psychophysical -Questionnaire Associationsmentioning
confidence: 99%
“…Researchers have realized that ASD is not only a disorder of brain, with the peripheral nervous, immune and metabolic systems playing a role in its pathogenesis, i.e. a disorder with systematic issues [13][14][15]. For example, one study with 32 autistic men indicated the participation of peripheral sensory nerves in etiology, possibly abnormal tactile sensation [13].…”
Section: Introductionmentioning
confidence: 99%